2018
DOI: 10.3389/fmicb.2018.00530
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiome Associates With Lipid-Lowering Effect of Rosuvastatin in Vivo

Abstract: Background: Statin has been widely used to treat hyperlipidemia because of its high potency in decreasing cholesterol levels. The present study aimed to examine the lipid-lowering effect of rosuvastatin and the composition, diversity and species abundance of gut microbiome in association with rosuvastatin efficacy. Trial registration: ChiCTR-ORC-17013212 at the First Affiliated Hospital of Dalian Medical University, November 2, 2017.Results: Totally 64 patients with hyperlipidemia were treated with 10 mg/day o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(70 citation statements)
references
References 54 publications
5
63
1
1
Order By: Relevance
“…Little is known about the direct effect of statins on the human gut microbiota, except for associations with overall bacterial composition in a population-based study 12 , and some differences between patients with and without normalization of blood lipid levels 26 . Herein, rosuvastatin treatment was associated with a trend towards increasing gut microbial richness, as reported in studies of atorvastatin-treated rats 5 , while studies in mice have been unable to detect changes in fecal microbial diversity after rosuvastatin treatment 27,28 .…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the direct effect of statins on the human gut microbiota, except for associations with overall bacterial composition in a population-based study 12 , and some differences between patients with and without normalization of blood lipid levels 26 . Herein, rosuvastatin treatment was associated with a trend towards increasing gut microbial richness, as reported in studies of atorvastatin-treated rats 5 , while studies in mice have been unable to detect changes in fecal microbial diversity after rosuvastatin treatment 27,28 .…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis at the phylum level found that ESM supplementation reduced Firmicutes, but increased Bacteroidetes and Cyanobacteria abundance. It has been reported that the phylum Firmicutes is negatively correlated with LDL‐cholesterol (Liu et al, 2018). Additionally, increased Bacteroidetes abundance has been implicated in the reduction of TG levels (Caspi et al, 2016), while increased Cyanobacteria abundance has been observed during prebiotic treatment (Everard et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the occurrence of certain bacterial species during dietary intervention, such as Lactobacillus spp., positively affects insulin sensitivity and reduces plasma cholesterol levels in obese mice (Park et al, 2017). A recent study involving hyperlipidaemia patients receiving rosuvastatin treatment showed that the hypolipidemic effect was associated with a variation in gut microbiota composition (Liu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The patient's statin-sensitive responses are linked to the gut microbiota, and the gut microbiota may guide the statin dosage adjustments [54]. There are indeed several reports showing that statins influence the diversity of the human gut microbiota [18,[55][56][57]. In addition, although the research on the antibacterial activity of FLU has been scarce and more studies are needed [58], it seems that its antifungal activity may be higher than that of other statins [59].…”
Section: Plos Onementioning
confidence: 99%